Co-Design: Understanding User Needs in Customizing Apparel and Accessories Products - Zainuddin Talani; Dwinita Larasati (fakultas Desain Komunikasi Visual, 2025)
Consumer involvement in product design through co-design strategies continues to evolve alongside advances in digital technology, particularly in the apparel and accessories industry. This process can be facilitated through digital platforms, specifically websites. This study aims to analyze and formulate web design strategies for co-design platforms that can accommodate consumer needs in the customization process of clothing and accessories. Using a descriptive qualitative method, this research examines consumer needs, which consist of clothing types, clothing parts, clothing details, and co-design tools within the co-design process. Additionally, it explores aspects of customer interface, visual elements, and usability in web interfaces. The findings from this analysis are then compiled to serve as a reference for the future development of co-design websites for apparel and accessories.